Internet censorship detected in Bangladesh (Bangladesh) - Voidly (2026)
CRITICAL severity censorship detected in Bangladesh. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: BD-2026-0206
Keywords: censorship; BD; censorship; critical